Pengembangan LKPD Berbasis Ramah Lingkungan Untuk Memberdayakan Kreativitas dan Kepedulian Lingkungan Siswa Kelas XI - Tomi; Mustika Sari; Tesa Manisa (LPD Universitas PGRI Pontianak, 2026)
This study was conducted to develop an environmentally friendly project-based Student Worksheet (LKPD) on the topic of the human respiratory system and to evaluate its validity, practicality, and effectiveness in enhancing the creativity and environmental awareness of eleventh-grade students at SMA Ngarimanan Sompak. The research adopted a Research and Development (R&D) approach based on the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants involved expert validators, biology teachers, and Grade XI students who participated in the product implementation. Data were collected using validation instruments, teacher and student response questionnaires, and pretest and posttest assessments. Descriptive statistical analysis was employed to determine the validity and practicality of the developed worksheet, while the Wilcoxon Signed Rank Test was used to examine its effectiveness. The findings revealed that the developed worksheet obtained an average validity score of 88.51%, indicating a highly valid category, and an average practicality score of 78.73%, categorized as practical. In addition, the Wilcoxon Signed Rank Test produced an Asymp. Sig. (2-tailed) value of 0.001 (p < 0.05), demonstrating a statistically significant improvement in students' learning outcomes after using the worksheet. These results suggest that the environmentally friendly project-based Student Worksheet is valid, practical, and effective for use in biology learning, particularly on the topic of the human respiratory system, to promote students' creativity and environmental awareness.